The Recovery of Thyroid Function in Low-Risk Papillary Thyroid Cancer After Lobectomy: A 3-Year Follow-Up Study - Dou, Yi; Chen, Yingji; Hu, Daixing; Su, Xinliang (Frontiers in Endocrinology, 2021)
Purpose Management strategies after lobectomy for low-risk papillary thyroid carcinoma (PTC) are controversial. This study aimed to identify the proportion of patients among low-risk PTC patients who do not require hormone replacement therapy and to evaluate the risk factors for postoperative hypothyroidism after lobectomy. Patients and Methods The records of 190 PTC patients who underwent thyroid lobectomy from January 2017 to December 2018 were retrospectively reviewed. Clinicopathological characteristics and follow-up data were collected. Univariate and multivariate analyses were performed to identify the risk factors associated with postoperative hypothyroidism and the recovery of thyroid function. Results In summary, 74.21% of patients (141/190) had normal thyroid function without levothyroxine supplementation, while 40.53% (77/190) developed temporary or permanent hypothyroidism. Multivariate analysis indicated that higher preoperative thyroid-stimulating hormone (TSH) levels (>2.62 mIU/L), Hashimoto’s thyroiditis (HT), and right lobectomy were associated with hypothyroidism (all P<0.05). The Area Under Curve (AUC) by logistic analysis was 0.829. Twenty-eight (28/77, 36.4%) patients recovered to the euthyroid state in the first year after surgery, and this recovery was significantly associated with preoperative TSH level. Forty-nine (49/77, 63.6%) patients developed persistent hypothyroidism. The thyroid function of most patients (11/28, 39.3%) recovered in the third month after surgery. Conclusion Patients with a lower level of preoperative TSH, with left lobectomy and without Hashimoto’s thyroiditis had a higher chance of normal thyroid function within the first year after lobectomy. The recovery of thyroid function was associated with the level of preoperative TSH.